2003
DOI: 10.1038/sj.cr.7290183
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MEK inhibitor U0126 on meiotic progression in mouse oocytes: microtuble organization, asymmetric division and metaphase II arrest

Abstract: In this study we used U0126, a potent and specific inhibitor of MEK, to study the roles of MEK/ERK/p90 rsk signaling pathway in the meiotic cell cycle of mouse oocytes. The phosphorylation of MAP kinase and p90 rsk in the oocytes treated with 1.5 M U0126 was the same as that in oocytes cultured in drug-free medium. With 1.5 M U0126 treatment, the spindles appeared normal as they formed in oocytes, but failed to maintain its structure. Instead, the spindle lost one pole or elongated extraordinarily. After furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 42 publications
2
51
1
Order By: Relevance
“…13 Deletion of MEK1/2 by intravenous and intrabursal injection of MEK inhibitor U0126 or MEK siRNA-injection treatment, causes large PB formation. 23,24 In the present study, we showed that GM130 was colocalized with p-MEK1/2 at MI and MII stages. The phenotypes in GM130 depletion oocytes were similar to what had been described in the deletion of p-MEK1/2 by U0126.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 62%
See 2 more Smart Citations
“…13 Deletion of MEK1/2 by intravenous and intrabursal injection of MEK inhibitor U0126 or MEK siRNA-injection treatment, causes large PB formation. 23,24 In the present study, we showed that GM130 was colocalized with p-MEK1/2 at MI and MII stages. The phenotypes in GM130 depletion oocytes were similar to what had been described in the deletion of p-MEK1/2 by U0126.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 62%
“…7A). Treatment of U0126, the specific MEK inhibitor, 24,25 caused disorganized spindles and GM130 dispersion into the cytoplasm in mouse oocytes.…”
Section: Sup Vid 6c)mentioning
confidence: 99%
See 1 more Smart Citation
“…MOS activity is required for normal microtubule organization before and during the MI/MII transition [15]. Direct inhibition of MEK during MI using the specific MEK inhibitor U0126 disrupts the MI spindle and causes formation of abnormally large first polar bodies similar to the mos -/-phenotype [16]. In addition, MOS/MEK/MAPK pathway components are physically associated with meiotic spindles, including phosphorylated ERK1/2 MAPK [17,18], phosphorylated MEK [19,20] and an ERK1/2 MAPK-interacting protein, DOC1R, whose depletion during MI causes formation of abnormal MII spindles [21].…”
mentioning
confidence: 99%
“…First observations were made in nullizygous mice for Mos, where MEK activation is impaired and interphase-like structure of microtubules and chromosomes are found between meiotic division, as well as formation of monopolar half-spindle (Araki et al, 1996;Tong et al, 2003;Verlhac et al, 1996). Similar observations were made in other biological systems.…”
Section: Amphibian Oocytesmentioning
confidence: 99%